Application of statistical analysis for parameter validation in measuring road network vulnerability performance - Santos, João Evangelista Dantas dos; Bertoncini, Bruno Vieira (Brazilian Journal of Production Engineering, 2024)
The form of the road network influences users’ travel time in interruption situations. Studies on road network vulnerability generally do not consider this characteristic, which can lead to incorrect conclusions. The objective of this work is to analyze the impact of choosing the performance parameter in the assessment of vulnerability, using regular and irregular networks as models. For this purpose, this work consisted of a literature review on road topology and road network vulnerability, modeling and simulation of two scenarios, and analysis of the results using descriptive statistics and parametric tests. Travel time proved to be a parameter sensitive to the form of the network, with the irregular network showing longer travel times than the regular network. On the other hand, the flow and speed parameters did not show significant differences between the networks. Choosing appropriate parameters is crucial to understanding the impact of interruptions on the transportation system. Travel time, being sensitive to the form of the network, should be considered in the planning and management of road networks. The results of this study assist in decision-making by public managers, communication with society, and the development of more resilient cities.